Mechanics of biosurfactant aided liquid phase exfoliation of 2D materials - Qian, Xuliang (2022)
Biosurfactant-aided liquid-phase exfoliation (LPE) is emerging as a biocompatible, green, economical, safe, and efficient approach to prepare two-dimensional (2D) materials for biomedical applications. However, relatively little is known about the molecular mechanisms of this process. Herein, we present the first study of how flavin mononucleotide (FMN) interacts with hexagonal boron nitride (hBN) nanosheets in the context of LPE. We demonstrate that FMN molecules can self-assemble on hBN via π-π interactions, as well as intermolecular hydrogen bonds (H-bonds) between the isoalloxazine moieties. Binding free energy analysis has shown FMN to be an efficient surfactant for LPE of hBN in water. According to the theoretical simulations, stable water suspension of hBN were experimentally obtained by LPE using FMN. With this work, we aim to exemplify how molecular dynamics (MD) simulation can predict and guide empirical LPE experiments, direct the surfactant screening and improve scalable production of 2D materials for biomedical applications.